Modeling foreign language curriculum: international internship research and program development: (Eurasian Journal of Philology Science and Education, 2024)
The article investigates how internship research programs promote global partnerships, culturalexchanges, and human development, focusing on the Minnesota English Language Program (MELP)practices in designing adaptable foreign language curricula. The research demonstrates the importanceof internships in enriching language programs and highlights how collaboration between internationaluniversities contributes to curriculum improvements. This approach aims to better prepare students forreal-world communication, fostering language proficiency and intercultural understanding.The article delves into the MELP’s excellent practices in designing foreign language teaching curricula adaptive to diverse contexts.The research studies the UMN and KBTU language course curricula and analyzes the survey data.The data provided statistical evidence to quantify identified features and shortcomings, contributing to adeeper understanding of the research questions.Based on the findings, the goal is to develop a new course curriculum for teaching the Kazakh language to non-native speakers in multicultural settings. The study adopts a mixed-methods approach,combining qualitative and quantitative methods, to comprehensively investigate the research objectives.Specifically, a survey was administered to 50 students from Narxoz University (Narxoz) and KazakhBritish Technical University (KBTU) to gather quantitative data on perceptions of the existing curriculum.Key words: internship program, Kazakh language course curriculum, MELP courses, mixed-methods, syllabus structure